Sea surface temperature and southwest monsoon over India (MAUSAM, 1991)
Importance of sea surface temperature (SST) over the Arabian Sea, Bay of Bengal and the north Indian Ocean is studied in relation with the formation and m1intenan';e of the southwest monsoon over India. SST over southeast Arabian Sea close to the west coast of India becomes maximum before the onset of monsoon over Kerala. Crossing of the equator by southern hemispheric warm water seems to be related with the early or late onset of the monsoon. Magnitude of the difference between SST and air temperature during pre-onset weeks gives valuable hints for early/late and excess/deficient monsoon. A large warm winter mass up to the depth of 100 metres shifts towards the west coast of India before the onset of the monsoon. In 1979, back and forth movement of this water mass seems to be related with the different phases of the monsoon over India.